Pengaruh Pelatihan, Kepuasan Kerja Dan Teamwork Terhadap Kinerja Karyawan Dengan Kepemimpinan Sebagai Variabel Moderasi (Pada PT. Indo Metro Surya Ando;a Kota Metro) - Dian Novita Sari; Sugeng; Suwarto; Fauzan Ramadhan (Universitas Muhammadiyah Metro, 2025)
Human resources who work in an organization or company have the ability to improve thequality of their performance, so that every employee who works in an organization mustreally be able to carry out factors that can help employees get the title with good qualityperformance. To achieve satisfactory employee performance, professional skills are neededto achieve it through several stages, in the world of organizations paying attention toemployee performance is something that is very important to do in achieving anorganizational goal or in increasing competitiveness and maintaining sustainability. researchsamples are employees of PT. Indo Metro Surya Andala Metro City. The research design is aquantitative research method used in this study is a survey and questionnaire. The populationand sample of this research are employees of PT. Indo Metro Surya Andala Metro City with apopulation of 70 and a sample of 56 employees. Data collection techniques using aquestionnaire. The analytical tool used is Regression Analysis. The results of the study showthat training, satisfaction and teamwork on employee performance with leadership as amoderating variable have a positive and significant effect on employees